Effects of Solvent and Reaction Time in Sonochemical Synthesis of Cadmium(II) Compounds and Use them as Template for Synthesis of Cadmium(II) Oxide Nano Structures. Issue 16 (1st April 2020) - Souri, Bagher; Rezvani, Ali Reza; Abbasi, Soheila; Hayati, Payam; Janczak, Jan
Abstract : Abstract . A cadmium(II) zero‐dimensional supramolecular compound [Cd(L)2 (I)2 ] (1 ), L = 2‐picolylamine, was fabricated by branch tube and sonochemical irradiation techniques. Regardless of the method utilized, the same crystallographic structure is obtained for the complex. To investigate the effects of reaction time and solvent on the creation of [Cd(L)2 (I)2 ] (1 ) supramolecule compound, certain tests were designed and four specimens of 1 were fabricated through sonochemical process. Less reaction time led to the creation of smaller particles with mixed morphologies. To prepare cadmium(II) oxide micro‐crystals via calcination, four samples were utilized as new precursors. Micro‐ and nano‐sphere of cadmium(II) oxide could be fabricated from 1. The morphology and structure of micro‐ and nano‐crystals were identified by using Scanning Electron Microscopy (SEM), IR spectroscopy, and X‐ray powder diffraction (XRD). Abstract :